Predicting Individual Susceptibility to Visually Induced Motion Sickness by Questionnaire - Golding, John F.; Rafiq, Aisha; Keshavarz, Behrang (Frontiers in Virtual Reality, 2021)
BACKGROUND The introduction of new visual technologies increases the risk of visually induced motion sickness (VIMS). The aim was to evaluate the 6-item Visually Induced Motion Sickness Susceptibility Questionnaire (VIMSSQ) and other predictors for individual susceptibility to VIMS. METHODS Healthy participants (10M+20F), mean age 22.9 (SD 5.0) years, viewed a 360 deg panoramic city scene projected in the visual equivalent to the situation of rotating about an axis tilted from the vertical. The scene rotated at 0.2Hz (72deg/s), with a ‘wobble’ produced by superimposed 18O tilt on the rotational axis, with a field of view of 84 deg. Exposure was 10 min or until moderate nausea was reported. Simulator Sickness Questionnaire (SSQ) was the index of VIMS. Predictors/correlates were VIMSSQ, Motion Sickness Susceptibility Questionnaire (MSSQ), Migraine (scale), Syncope, Social & Work Impact of Dizziness (SWID), Sleep quality/disturbance, Personality (‘Big Five’ TIPI), a prior multisensory Stepping-Vection test, and Vection during exposure. RESULTS The VIMSSQ had good scale reliability (Cronbach’s alpha=0.84). and correlated significantly with the SSQ (r=0.58). Higher MSSQ, Migraine, Syncope & SWID also correlated significantly with SSQ. Other variables had no significant relationships with SSQ. Regression models showed that the VIMSSQ predicted 34% of the individual variation of VIMS, increasing to 56% as MSSQ, Migraine, Syncope and SWID were incorporated as additional predictors. CONCLUSIONS The VIMSSQ is a useful adjunct to the MSSQ in predicting VIMS. Other predictors included Migraine, Syncope & SWID. No significant relationship was observed between Vection and VIMS.